Stroke care: Room for improvement. Issue 3 (15th February 2016) - Heuser, Richard
Key Points: Endovascular devices to treat stroke will continue to improve Stroke care is suboptimal with IV TPA with such a narrow treatment window Interventional cardiologists should be involved in stroke care with appropriate training.